ศักยภาพของสำนักงานบัญชีในเขตภาคเหนือตอนล่าง สำหรับการเป็นสำนักงานบัญชีคุณภาพ / The Potential of Accounting Firms in Lower-Northern Region For the Accredited Accounting Firms - Supaporn Dokmaithong and Warawit Phetruen, สุภาพร ดอกไม้ทอง และวรวิทย์ เพ็ชรรื่น / (Journal of Community Development Research (Humanities and Social Sciences), 2017)
การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาศักยภาพของสำนักงานบัญชีในเขตภาคเหนือตอนล่างในการเป็นสำนักงานบัญชีคุณภาพ โดยพิจารณาการปฏิบัติตามเกณฑ์ควบคุมคุณภาพของกรมพัฒนาธุรกิจการค้า กระทรวงพาณิชย์ กลุ่มตัวอย่างเป็นสำนักงานบัญชีในเขต 9 จังหวัด ภาคเหนือตอนล่างที่ยังไม่ได้ขอการรับรองคุณภาพและเก็บข้อมูลโดยใช้แบบสอบถาม จากการศึกษา พบว่า กลุ่มตัวอย่างมีคุณภาพโดยรวมอยู่ในระดับดี เมื่อแยกพิจารณาตามองค์ประกอบแต่ละด้านของระบบควบคุมคุณภาพ พบว่า มีคุณภาพอยู่ในระดับ ดี ถึง ดีมาก ซึ่งสามารถพิจารณาได้ว่า กลุ่มตัวอย่างมีศักยภาพในการเป็นสำนักงานบัญชีคุณภาพ การวิเคราะห์เพิ่มเติมถึงปัจจัยที่มีผลต่อคุณภาพโดยศึกษา 3 ปัจจัย ประกอบด้วย ประสบการณ์ในการประกอบธุรกิจ รูปแบบการประกอบธุรกิจ และขนาดของสำนักงาน จากการวิเคราะห์ถดถอยเชิงพหุ พบว่า ประสบการณ์ในการประกอบธุรกิจส่งผลกระทบเชิงบวกอย่างเป็นสาระสำคัญต่อคุณภาพโดยรวม และเมื่อพิจารณาคุณภาพแยกตามแต่ละองค์ประกอบของระบบควบคุมคุณภาพ พบว่า ประสบการณ์ในการประกอบธุรกิจส่งผลกระทบเชิงบวกอย่างเป็นสาระสำคัญต่อคุณภาพในหลายด้าน คือ คุณภาพด้านความรับผิดชอบของผู้บริหาร ด้านข้อกำหนดทางด้านจรรยาบรรณ ด้านกระบวนการที่เกี่ยวกับลูกค้า และด้านการปฏิบัติงาน นอกจากนี้ยังพบว่าการประกอบธุรกิจในรูปแบบนิติบุคคล มีผลกระทบเชิงบวกอย่างเป็นสาระสำคัญต่อคุณภาพด้านกระบวนการที่เกี่ยวกับลูกค้า และด้านการปฏิบัติงาน ในทางตรงกันข้าม ขนาดของสำนักงานส่งผลกระทบเชิงลบอย่างเป็นสาระสำคัญต่อการปฏิบัติด้านข้อกำหนดทางด้านจรรยาบรรณของสำนักงาน      The purpose of this research is to study the potential of accounting firms in the lower-northern region for an accredited accounting firm. We base the study on the quality control system of the Department of Business Development, the Ministry of Commerce. A sample consists of accounting firms in nine provinces of the lower-northern region that has not been accredited. We find that the overall quality score is in good level. Considering each quality control element, we find that the scores are between good to very good levels. It is possible to consider that the sample has a potential for accreditation. An additional regression analysis for factors affecting the quality including firm experience, business form, and firm size shows that firm experience has a significantly positive effect on the overall quality. Considering each quality control element, we find that firm experience has a significantly positive effect on several elements regarding management responsibility, ethical requirements, client engagement process, and engagement performance. In addition, we find that running an accounting firm as a corporate entity has a significantly positively effect on client engagement process, and engagement performance. However, firm size has a significantly negative effect on quality regarding ethical requirements.
Keywords: คุณภาพ สำนักงานบัญชีคุณภาพ ภาคเหนือตอนล่าง การควบคุมคุณภาพ ศักยภาพ; Quality, Accredited Accounting Firm, Lower-Northern Region, Quality Control, Potential